Using SPE-LC-ESI-MS/MS analysis to assess disperse dyes in environmental water samples - Zocolo, Guilherme Julião [UNESP]; Pilon dos Santos, Glauco [UNESP]; Vendemiatti, Josiane; Vacchi, Francine Inforçato; Umbuzeiro, Gisela de Aragão; Zanoni, Maria Valnice Boldrin [UNESP] (Published by Oxford University Press. All rights reserved. For Permissions, please email: journals.permissions@oup.com., 2015)
We have optimized an SPE-LC-ESI-MS/MS method and used it to monitor disperse azo dyes in environmental aquatic samples. Calibration curves constructed for nine disperse dyes-Red 1, Violet 93, Blue 373, Orange 1, Orange 3, Orange 25, Yellow 3, Yellow 7 and Red 13-in aqueous solution presented good linearity between 2.0 and 100.0 ng mL(-1). The method provided limits of detection and quantification around 2.0 and 8.0 ng L(-1), respectively. For dyes at concentrations of 25.0 ng mL(-1), the intra- and interday analyses afforded relative standard deviation lower than 6 and 13%, respectively. The recovery values obtained for each target analyte in Milli-Q water, receiving waters and treated water samples spiked with the nine studied dyes at concentrations of 8.0, 25.0 and 50.0 ng L(-1) (n = 3) gave average recoveries greater than 70%, with RSD <20%. Statistical evaluation aided method validation. The validated method proved to be useful for analysis of organic extracts from effluents and receiving water samples after an SPE extraction step. More specifically, the method enabled detection of the dyes Disperse Red 1, Disperse Blue 373 and Disperse Violet 93 at concentrations ranging from 84 to 3452 ng L(-1) in the treated effluent (TE), affluent and points collected upstream and downstream of the drinking water treatment plant of a textile dye industry in Brazil.